Effect of aerobic exercise on blood lipid levels in postmenopausal women - Mawi, Martiem (Faculty of Medicine, Trisakti University, 2009)
High blood total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C) and triglycerides (TG), and low concentrations of high-density lipoprotein cholesterol (HDL-C) are related to risk for coronary heart disease (CHD) development. Growing evidence indicates that physical exercise can prevent at least some of the negative effects on health associated with post. The purpose of this study was to evaluate the effect of regular aerobic exercise for 12 weeks on the levels of total cholesterol (TC), low-density lipoprotein cholesterol (LDL-C), high-density lipoprotein cholesterol (HDL-C), and triglycerides. An experimental study was conducted comprising 62 postmenopausal women, aged 50-70 years, not on hormonal therapy, consuming a regular diet, living in East and South Jakarta, and willing to perform aerobic exercises regularly. The results of this study showed that all four lipid levels differed significantly between the control group and the intervention group, the respective mean levels ± SD for TC being 228.0 ± 39.7 mg/dL vs. 171.6 ± 18.4 mg/dL, (p = 0.000); for LDL-C 149.0 ± 36.9 mg/dL vs. 97.7 ± 17.8 mg/dL, (p = 0.000); for HDL-C 50.9 ± 3.9 mg/dL vs. 71.5 ± 6.7 mg/dL, (p = 0.000); and for triglycerides 150.5 ± 67.5 mg/dL vs. 95.0 ± 37.8 mg/dL (p = 0.000). Thus practitioners recommending exercise for coronary artery disease risk reduction in postmenopausal women.